PEDAGOGICAL CONDITIONS OF SOCIALIZATION OF CHILDREN OF SENIOR PRESCHOOL AGE IN THE INTERACTION OF PRESCHOOL EDUCATION INSTITUTION AND FAMILY - Ivakh, Svitlana; Fedorovych, Anna; Tytarenko, Svitlana; Palasevych, Iryna; Kalichak, Yuriy (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Rapid socio-political changes in the life of modern society make it necessary to prepare children for the development of social relations and various types of behavior in society from an early age. Such qualities as the ability to manage their behavior and ways of communication, the ability to choose appropriate behavior, orientation in new circumstances, a sense of their place among other people is the sphere of social development of the child, which contributes to their social well-being. The effectiveness of the implementation of the outlined tasks of social development of preschoolers is largely determined by the establishment of interaction between preschool education institutions and families of pupils. Only close relations of the preschool education institution on the basis of cooperation with the family provide conditions for the full process of socialization of the preschool child. Our research allowed us to find out the existing problems in socialization of the majority of children of senior preschool age, in particular: unformed ideas about "approved", "acceptable" and "unacceptable" forms of behavior; inability to establish and maintain positive relationships with others; short-term and unstable relationships with peers; unformed positive attitude to society and themselves; inability to solve problem situations. Purpose of article is to substantiate the psychological and pedagogical conditions for the socialization of the personality of a child of senior preschool age in the process of interaction between the family and the institution of preschool education. To achieve this goal, a number of theoretical and empirical methods were used: theoretical: analysis, systematization, and generalization of theoretical data presented in the psychological and pedagogical literature; empirical: a survey of educators using the method of T. Repina (2004), sociometric study "Birthday", observation of children's behavior in joint activities and games.  In the process of organizing the work, the following methods and techniques have proved their effectiveness: organization of positive communication between parents, educators and children; involvement of parents in assessing the child's progress, forecasting the prospects for the child's development; encouraging parents to participate in joint work with the child and the teacher, the staff of the preschool institution; active listening to parents, trying to understand their problems, to help make a well-grounded pedagogical decision; building friendly, optimistic, cordial relations with parents.